Tri Hita Karana as a form of pro-environmental behavior in Bindu Traditional Village - Anggana, I Putu Surya; Mudana, I Gede; Triyuni, Ni Nyoman; Sukmawati , Ni Made Rai (Politeknik Negeri Bali, 2022)
This research aims to describe the pro-environment behavior based on the Tri Hita Karana concept in Bindu Traditional Village, Badung, Indonesia. This type of research uses a qualitative descriptive method to explain Tri Hita Karana as a form of pro-environmental implementation in Bindu Traditional Village. The results show that the implementation of pro-environmental behavior in the form of Tri Hita Karana teachings in people's lives in the Parhyangan (aspects of God) is realized by worshiping and serving the God, in the Pawongan (aspects of human) by helping each other and working together with humans, and in the Palemahan (aspects of natural environment) by preserving nature.